Current and future immunotherapy approaches in ovarian cancer - (:unkn) unknown (AME PUBL CO, 2020)
Ovarian cancer (OC) is the major cause of gynecologic cancer deaths and relapse is common despite advances in surgery and systemic chemotherapy. Therefore, novel treatments are required to improve long-term outcomes of the disease. Efficacy of immunotherapy was demonstrated in many tumors and it has been since incorporated into clinical practice for them. Although early data form preclinical studies imply that OC has an immunogenic microenvironment, immune checkpoint inhibitors (ICIs) did not produce favorable results in clinical trials to date. This review will highlight data from clinical studies regarding immunotherapy in OC and its combination with other agents as well as immunologic prospects which could strengthen the therapeutic armament against the disease in the future.
Keywords: Immune checkpoint inhibitors (ICIs); immunotherapy; ovarian cancer (OC); ENDOTHELIAL GROWTH-FACTOR; PEGYLATED LIPOSOMAL DOXORUBICIN; T-CELLS; PLATINUM-RESISTANT; ANTITUMOR-ACTIVITY; CLINICAL ACTIVITY; PD-L1 EXPRESSION; DENDRITIC CELLS; REGULATORY T; COMBINATION